2007
DOI: 10.1158/0008-5472.can-06-4350
|View full text |Cite|
|
Sign up to set email alerts
|

The Tyrosine Phosphatase Shp2 Interacts with NPM-ALK and Regulates Anaplastic Lymphoma Cell Growth and Migration

Abstract: Anaplastic large cell lymphomas (ALCL) are mainly characterized by the reciprocal translocation t(2;5)(p23;q35) that involves the anaplastic lymphoma kinase (ALK) gene and generates the fusion protein NPM-ALK with intrinsic tyrosine kinase activity. NPM-ALK triggers several signaling cascades, leading to increased cell growth, resistance to apoptosis, and changes in morphology and migration of transformed cells. To search for new NPM-ALK interacting molecules, we developed a mass spectrometry-based proteomic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 41 publications
3
65
1
4
Order By: Relevance
“…Importantly, these mutant proteins were as efficient as wt IKAROS at rescuing abnormal phenotypes from homozygous mutant mice, suggesting that the IK L allele is mainly, if not exclusively, a loss of function allele. 7,8 Two cohorts of BCR-ABL ĂŸ compound mice were generated that carried either two alleles of wt IKZF1 (BCR-ABL ĂŸ /0 ; IK ĂŸ / ĂŸ ), or one wt and one mutant IKZF1 allele (BCR-ABL ĂŸ /0 ; IK L/ ĂŸ ), which were compared for leukemia development. Nontransgenic IK ĂŸ / ĂŸ and IK L/ ĂŸ littermates were included as controls.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these mutant proteins were as efficient as wt IKAROS at rescuing abnormal phenotypes from homozygous mutant mice, suggesting that the IK L allele is mainly, if not exclusively, a loss of function allele. 7,8 Two cohorts of BCR-ABL ĂŸ compound mice were generated that carried either two alleles of wt IKZF1 (BCR-ABL ĂŸ /0 ; IK ĂŸ / ĂŸ ), or one wt and one mutant IKZF1 allele (BCR-ABL ĂŸ /0 ; IK L/ ĂŸ ), which were compared for leukemia development. Nontransgenic IK ĂŸ / ĂŸ and IK L/ ĂŸ littermates were included as controls.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Of note, a recent massspectrometry approach identified PTPN11 as a substrate of NPM/ALK. 7 (c) G-banded chromosomes 2 and FISH analysis of patient 6 using the VYSIS LSI ALK Dual Color, Break Apart Probe and chromosome arm specific (CAP) for 2p (green) and 2q (red) probes, respectively. In interphases, one fusion and a red and a green signal were found; metaphases showed that the 3 0 ALK signal (red) was translocated on the q-arm of the other chromosome 2 and CAP probes also confirm the translocation t(2;2).…”
mentioning
confidence: 99%
“…However, ROS production has never been investigated downstream of ALK. As signaling molecules, ROS were shown to oxidize critical targets for cell invasion, such as PTPs, MAPK, phosphate and tensin homolog (PTEN) or the Rac effector p21-activated kinase (PAK, proteins that are also affected by NPM-ALK (Honorat et al, 2006;Wu, 2006;Voena et al, 2007). We therefore sought to analyse the levels of ROS in NPM-ALK( ĂŸ ) cells.…”
mentioning
confidence: 99%
“…34,35 Overexpression of SHP2 is also detected in samples from patients with leukemia and diffuse large B-cell lymphoma. [36][37][38] However, the relative expression and functional impact of SHP2 in B-cell lymphomagenesis remains unknown.…”
Section: Critical Role Of Shp2 (Ptpn11) Signaling In Germinal Center-mentioning
confidence: 99%
“…Immunoblotting and immunoprecipitation analysis were performed as described previously. 38 The electrophoretic mobility shift assay (EMSA) was conducted with 32 P-dATP-labeled oligonucleotide probes (Online Supplementary Table S2) and the products were separated on a native polyacrylamide gel.…”
Section: Immunoblotting Immunoprecipitation and Electrophoretic Mobimentioning
confidence: 99%